PENGEMBANGAN MODUL BERBASIS SETS PADA MATERI GELOMBANG BUNYI DAN CAHAYA KELAS XI SMA DALAM UPAYA MENINGKATKAN LITERASI TEKNOLOGI - Rahayuni, Nurgus; Irianti, Mitri; Ma’aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
The SETS-Based Module is a teaching material that is systematically arranged in language that is easily understood by students according to their level of understanding and age so that it can be used for independent study. This module is structured using a SETS (Science, Environment, Technology and Society) approach which is integrated with each other. This SETS-based module consists of material descriptions, interesting experiments, questions and discussions, practice questions and articles containing technological literacy. The purpose of this research is to produce teaching materials in the form of SETS-based modules that are valid and suitable for use in physics learning in class XI SMA on Sound and Light Waves in an effort to improve students' technological literacy. This type of research is Research and Development (R&D) using a 4D development model. The research instrument used in this study was a module validation sheet. Quantitative and qualitative data were obtained from the results of the validator's assessment. The results showed that the SETS-based module development on sound and light waves was valid with a score of 3.41. Thus the SETS-based module on Class XI Sound and Light Waves in an effort to improve technological literacy can be declared valid and worthy of testing in physics learning.Keywords: Module Development, SETS, Sound and Light Waves, Technology Literacy